A novel technique for the optimization and reduction of gamma spectroscopy geometry uncertainties. (February 2020) - Frosio, Thomas; Menaa, Nabil; Bertreix, Philippe; Rimlinger, Maeva; Theis, Chris
Abstract: Material activation can sometimes cause large heterogeneities in the distribution of radioactivity (hotspots). Moreover, the sample geometry parameters are not always well known. When performing gamma-spectroscopy to quantify the radionuclide inventory in activated materials, often predefined models are used to represent the sample geometry (dimensions, source-to-detector distance, material type) and their activity distribution, for efficiency calibration. This simplification causes uncertainties of the efficiency curves associated with the model and consequently, to the activity results. In this paper, we develop a new approach, based on ISOCS/LabSOCS to quantify and reduce uncertainties originating from the geometry model. The theory is described in this document and an experimental case is discussed. Highlights: Gamma-spectroscopy geometric model uncertainty quantification. Gamma-spectroscopy geometric model uncertainty optimization. Multi-count and activity consistency. Efficiency calibration. High purity germanium detector.